Demographic Analysis of Benign Paroxysmal Positional Vertigo as a Common Public Health Problem - Yetiser, S (Ann Med Health Sci Res, 2015)
BACKGROUND: Benign paroxysmal positional vertigo (BPPV) is the most common peripheral vestibular problem. However, demographic analysis is few. AIM: The aim of this study was to document the demographic data of patients with BPPV regarding distribution of gender, age, associated problems, most common form, symptom duration, severity of nystagmus and cure rate. SUBJECTS AND METHODS: A total of 263 patients with video-nystagmography confirmed BPPV were enrolled in this retrospective study (2009-2013). The data were collected in Anadolu Medical Center. Distribution of gender, age and affected side were reviewed. Associated problems were noted. Patients were analyzed according to the canal involvement, age, duration of symptoms, duration of nystagmus and recurrence. Mean values and standard deviations were calculated. One-way ANOVA test was used for the analysis of the data (Statistical Package for the Social Sciences 17.0 version, IBM, Chicago, III, USA). Statistical significance was set at P < 0.05. RESULTS: Women were affected more frequently than men (1:1.5). Comparative analysis of average age between the two gender groups was not statistically significant (P = 0.84). BPPV was common at middle age group. The incidence of affected side was not significant (P = 0.74). Posterior canal-BPPV (PC-BPPV) was the most leading one (129/263; 49%) followed by lateral canal (LC)-canalolithiasis (60/263; 22.8%), LC-cupulolithiasis (38/263; 14.5%) and superior canal-BPPV (9/263; 3.4%). 55.1% of patients were defined as idiopathic (145/263). Associated problems were migraine (31/263; 11.8%), trauma (19/263; 7.2%), inner ear disorders (18/263; 6.8%) and other systemic problems (50/263; 19.1%). 72.6% of patients had symptoms <2 months (191/263). 23,6% of patients had intensive nystagmus lasting more than a minute regardless of canal involvement (62/263). 33% of patients required two or more maneuvers for the relief of symptoms (87/263). CONCLUSION: Symptoms are prone to recur in those of traumatic origin, associated inner ear problems and systemic disorders. As the prognostic factors are illuminated, preventive measures will be more effective and more patients will be cured properly.